النظرية الاجتماعية ومعوقات تطبيقها من اجل مقاربة ابستيمولوجية - لطرش، ليلى; سليماني، صبرينة (University Of Eloued جامعة الوادي, 2022)
أن تطور الفكر السوسيولوجي ارتبط بمتغيرات اقتصادية واجتماعية وسياسية خاصة في أوروبا وفي هذا السياق تطور مفهوم النظرية الاجتماعية من مجموع افتراضات أو عبارات علائقية إلى أشكال رياضية تتكون من مقدمات ومعادلات, إلا أن صياغتها اصطدمت إلى اليوم بصعوبات على المستوى المفهمي والتطبيقي لتعقد فهمها وتقعيدها (تجسيدها) في الحق السوسيولوجي المليء بالمشكلات المعقدة في بنيتها و مؤثراتها ,وقد أصبح للنظرية الاجتماعية عدة ادوار في تفسير الظواهر والسلوكات البشرية وتأويل ما يمكن اكتشافه وملاحظته ووصف الأشياء والأحداث كما في الواقع ,إذ أصبحت تقدم معارف معينة في المجال الاجتماعي وتجسد خبرات المنظرين واهتماماتهم وتحث روح التأمل وفهم الواقع واقتراح فرضيات لما قد يكون عليه الواقع ,بل أصبحت تسعى لاكتساب المرونة النظرية أي إمكانية استخدامها في النقاشات العقلانية وهذا ما يضفي دورا جديدا لها وهو إمكانية تطبيقها في حل الصراعات والمشكلات الاجتماعية. إلا أن عملية بنائها وصياغتها تواجه صعوبة في فهم المفاهيم و كيفية بناء مفاهيم إجرائية للمفاهيم المكونة للنظرية للتمكن من قياس العلاقات بين المتغيرات أي عدم الاكتفاء باكتشاف وجود علاقة بينهما بل قياس هذه العلاقة , ما أدى إلى افتقار النظرية الاجتماعية للاستنباط ومعرفة تأثير مختلف العوامل المتدخلة أو المؤثرة في الظاهرة أي الاكتفاء بوصف العلاقة دون تفسيرها. وهذا ما شكل صعوبة في تطبيق النظرية الاجتماعية في البحوث الاجتماعية لصعوبة فهمها وصعوبة التفسير دون تأثر الباحث بالجانب ألقيمي وارتباطاته الأخلاقية وانتماءاته السياسية مما يؤثر على موضوعية النظرية في حد ذاتها.لهذا و بهدف تبسيط توظيف النظرية قدمنا هذه الورقة البحثية لتحديد مختلف صعوبات تطبيق النظرية الاجتماعية في البحوث الاجتماعية وتذليلها أما الطالب والباحث والتمكن من بذل جهود اكبر في فهم وتوظيف النظرية بشكل صحيح ينعكس على نتائج البحث السوسيولوجي و يساهم في بلوغ درجة من التوافق والملاءمة بين الموضوع ومنهج الدراسة والنظريات المستخدمة في البحث. Summary : The development of sociological thought was linked to economic, social and political variables, especially in Europe. In this context, the concept of social theory has developed from a set of relational assumptions or phrases to mathematical forms consisting of premises and equations. However, its formulation collides with difficulties at the conceptual and applied level, due to the complexity of its understanding and its personification. In the sociological right, which is full of complex problems in its structure and effects. Social theory has played several roles in explaining human phenomena and behaviors, interpreting what can be discovered and observed, and describing things and events as they are in reality. It is seeking to gain theoretical flexibility, that is, the possibility of using it in rational discussions, and this gives it a new role, which is the possibility of applying it in solving conflicts and social problems. However, the process of its construction and formulation faces difficulty in understanding the concepts and how to build procedural concepts for the concepts that make up the theory in order to be able to measure the relationships between the variables, i.e. not only discovering the existence of a relationship between them, but rather measuring this relationship, which led to the social theory’s lack of deduction and knowledge of the impact of the various intervening or influencing factors In any phenomenon, it is sufficient to describe the relationship without explaining it.This is what constituted a difficulty in applying social theory in social research due to the difficulty of understanding it and the difficulty of interpretation without the researcher being affected by the ethical aspect, his moral connections and his political affiliations, which affects the objectivity of the theory in itself. Therefore, and in order to simplify the application of the theory, we presented this research work to determine what are the difficulties of applying social theory in social research With the aim of overcoming it, as for the student and researcher, and being able to make greater efforts in understanding and using the theory correctly. It is reflected in the results of sociological research and contributes to achieving a degree of compatibility and relevance between the subject, the study curriculum, and the theories used in the research.
مداخلة
Keywords: النظرية الاجتماعية; تطبيق النظرية; البحث السوسيولوجي; social theory; theory application; sociological research